Peningkatan Kompetensi Manajerial Sumber Daya Manusia Melalui Pelatihan Berbasis Kompetensi Pada Umkm Di Kota Tasikmalaya - Taufik Hermansyah; Iwan Saputra; Siti Amirah Makarim; Lati Sari Dewi (CV. SINAR HOWUHOWU, 2026)
This community service activity aims to enhance the managerial competencies of human resources (HR) among micro, small, and medium enterprises (SMEs) in Tasikmalaya City through a competency-based training program. The identified problems include low capability in HR planning, recruitment, performance evaluation, and employee development. The methods used include participatory training, direct mentoring, case studies, and management simulations. The activity was conducted over three days on March 15–17, 202, in Cipedes District, Tasikmalaya City, involving 45 participants from various SME sectors. Results showed a significant improvement in participants' understanding of HR management concepts, with the average pretest score increasing from 52.4 to 78.6 on the posttest (a 49.6% improvement). A total of 91% of participants expressed satisfaction with the training and committed to applying the acquired knowledge in their business units. This activity is expected to contribute to the sustainable enhancement of SME competitiveness in Tasikmalaya City.